The Role Of Islamic Religious Education Teachers In Installing Students' Discipline Character Values At MIN 4 Way Jepara Lampung Timur - Umi Fadhilah; Damanhuri Damanhuri; Septiani Selly Susanti (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This study aims to analyze the role of Islamic Religious Education teachers in instilling discipline character values ​​in students at MIN 4 Way Jepara, Lampung Timur. The method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The subjects of the study included Islamic Religious Education teachers and students at the school. The results of the study indicate that teachers act as demonstrator, class manager, mediator, facilitator, and evaluator in the process of instilling disciplined character. The methods applied include role models, advice, discussion, and a love approach. The main challenge faced is the low personal awareness of students who are still in the development stage. Instilling disciplined character values ​​has been proven to significantly increase discipline and shape students' moral and spiritual character. This study confirms that the role of Islamic Religious Education teachers is crucial in instilling disciplined character values, which contribute to the formation of student character at MIN 4 Way Jepara, Lampung Timur.